Prevalence and risk factors of trastuzumab induced cardiotoxicity in Tunisian HER2-positive breast cancer patients. (April 2023) - Toukabri, Imen; Ben Said, Azza; Hamdi, Adel; Aloulou, Aziza; Ben Ayed, Wiem; Cherif, Ines; Limayem, Imen
Introduction: Cardiotoxicity is the most important side effect of Trastuzumab treatment. The purpose of this study is to evaluate the prevalence of Trastuzumab induced cardiotoxicity and to analyze risk factors associated with this side effect. Materials and Methods: A retrospective institutional study was carried out from June 2018 to December 2018 at the department of Medical Oncology of Salah Azaiz institute, Tunis, Tunisia. Demographic, clinical characteristics (menopausal status, breast cancer stage, anthracyclines exposure, comorbidities presence…) and left ventricular ejection function (LVEF) measurements, were collected from patient records. Results: Twenty-three women (20%) had Trastuzumab induced cardiotoxicity.65.2% (N = 15) experienced a decrease in LVEF more than 10% with a decrease below normal value and 34.8% (N = 8) experienced a decrease in LVEF more than 20%. Obesity is a risk factor for the occurrence of Trastuzumab induced cardiotoxicity (adjusted odds ratio (OR) = 2.919 (95% confidence interval (CI) [1.0411–8.186]; p = 0.042). Conclusion: Our study highlighted that obesity is associated with a high risk of cardiotoxicity in women treated with Trastuzumab. Therefore, close monitoring of cardiac function is recommended especially for obese women during Trastuzumab administering.